Value Chain Analysis of the Hajj Economic Ecosystem: Accommodation, Transportation, Consumption, and Retail - Musnawati (Journal of Emerging Economics and Business, 2026)
Indonesia's position as the world's largest sender of Hajj pilgrims, dispatching over 220,000 pilgrims annually from a Muslim population of roughly 244.7 million, places the Hajj-Umrah ecosystem at the center of a multi-trillion-rupiah economy extending beyond religion into banking, accommodation, transportation, and trade. Yet studies systematically integrating this economic multiplier effect with institutional governance challenges remain limited. This study analyzes the strategic role of Indonesia's Hajj-Umrah ecosystem as a multi-sector economic driver while identifying its accompanying governance challenges. A qualitative, descriptive-analytical design was employed, combining primary data from in-depth interviews and focus group discussions with key stakeholders, and secondary data from academic journals, institutional reports, and comparative case studies from Malaysia and Pakistan, with informants selected via purposive sampling and data analyzed through thematic coding and triangulation. Findings reveal six interconnected components travel agencies, accommodation, transportation, Islamic finance, religious tourism, and commodity trade each with distinct contributions and constraints. Growth proves asymmetric: Islamic finance and accommodation, anchored by mature institutions like BPKH, show accelerating performance, while religious tourism and commodity trade remain hindered by fragmented governance. These results refine the transnational multiplier effect framework by showing institutional maturity, not sectoral scale alone, drives differential outcomes. The study recommends strengthening lagging components and conducting further quantitative, cross-country research.